Reconceptualizing momentary engagement through the lens of conceptual change learning - Natassa / Anastasia Kyriakopoulou (Frontline Learning Research)
This commentary reviews the five papers featured in this special issue, which foster a cross-disciplinary discussion on momentary engagement (ME). The papers represent diverse theoretical perspectives and address key research questions central to understanding students’ ME. The commentary approaches each paper through the lens of conceptual change, focusing on the learning processes needed when the information to be acquired is inconsistent with the existing theoretical frameworks. Methodological challenges in measuring ME within the context of conceptual change are explored, moving beyond traditional acquisition type of learning. The variation in quality and depth of momentary engagement is also discussed, distinguishing between different modes of active learning and engagement. Further attention is given to the complex, dual role of factors such as learner characteristics, prior knowledge, and epistemic beliefs in shaping ME, especially in domains requiring radical reorganization of initial beliefs. Finally, the potential for constructing an integrated model of ME is discussed, in alignment with the holistic approach to ME implied by the papers in this issue. The author emphasizes the importance of studying ME’s interconnected components within both the individual and the context, employing varied methodologies and accounting for different learning types. The implications of integrating different theoretical frameworks are discussed in relation to developing interventions aimed at enhancing students’ ME in the classroom context.